ANALISIS PENGARUH PROMOSI, DESAIN PRODUK, DAN KELOMPOK REFERENSI TERHADAP KEPUTUSAN PEMEBELIAN DENGAN CITRA MEREK SEBAGAI VARIABEL INTERVENING - Ayuningtyas, Rizky; Magnadi, Rizal Hari (Faculty of Economics and Business Diponegoro University, 2016)
Intenese competition has made Ades bottledÂ water which is the Integration which has been acquired by PT. Coca Cola Amatil has precentage decreasing of Top Brand Index (TBI) for threeÂ years and always be in the last rankÂ for the Top Four of bottled water in Indonesia. Top Brand Index (TBI) has three main indicators, namely Commitment Share, Mind Share and Market Share.The purpose of this study is to determine the influence of variables Promotion, Product Design, and Reference Group can increase the percentage of TBI. Variable Promotion, Product Design, and the Reference Group as an independent variable; Brand image as an intervening variable; and Purchase Decision as the dependent variable.The population used in this research is the consumer of bottled water Ades. This research method using a non-probability sampling technique by purposive sampling method. Used as a sample 157 respondents. Data obtained from the questionnaire which is then processed and analyzed using SEM (Structural Equation Modeling) through AMOS program.The results showed that all three of independently variable has a positive influence on brand image; and Brand have a positive influence on the buying decision. Of the three independent variables influence the Reference Group has the greatest impact on brand image, and then followed by the promotion and the smallest is the Product Design.